Determining patterns in the influence of the geometrical parameters of the connecting pipeline on the dynamic parameters of the pneumatic spring of railroad rolling stock - Kuzyshyn, Andrii; Kovalchuk, Vitalii; Stankevych, Volodymyr; Hilevych, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is the process of determining the dynamic indicators of the pneumatic spring, which is used as the main element of the second stage of spring suspension in the high-speed rolling stock of the railroad, based on the influence of the geometric parameters of the connecting pipeline. It has been established that the dynamic indicators of rolling stock mainly depend on the operation of the pneumatic spring, the characteristics of which are largely determined by the geometric parameters of the connecting element between the pneumatic spring and the additional tank. A mathematical model of oscillations of a dual-mass system has been constructed, the elements of which are connected through a pneumatic spring suspension system. The operation of the pneumatic system is described using the Boyle–Mariotte equations, the state of the ideal gas, the energy for the flow in the connecting pipeline, and the law of conservation of energy. Theoretical studies into the influence of the diameter and length of the connecting element of the pneumatic spring suspension system on energy loss and damping coefficient for the cycle of its operation and the rigidity of the pneumatic spring have been carried out. It was established that the dependence of the stiffness of the pneumatic spring, while changing the value of the diameter of the connecting element from 6 mm to 30 mm, is nonlinear. In the process of compression, the rigidity of the pneumatic spring changes with the length of the connecting element of 1 m from 927 kN/m, static rigidity, to 497 kN/m, dynamic rigidity. The dependences of energy loss and damping coefficient for the operation cycle of the pneumatic spring suspension system based on the hysteresis loop have been constructed. It was found that the difference between the damping coefficient in the process of compression and expansion of the pneumatic spring is no more than 4 %. It was established that the design of high-speed rolling stock is impossible without high-quality modeling of the process of operation of the pneumatic spring suspension system